2011
DOI: 10.1186/1471-2202-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation of the prefrontal cortex modulates working memory performance: combined behavioural and electrophysiological evidence

Abstract: BackgroundTranscranial direct current stimulation (tDCS) is a technique that can systematically modify behaviour by inducing changes in the underlying brain function. In order to better understand the neuromodulatory effect of tDCS, the present study examined the impact of tDCS on performance in a working memory (WM) task and its underlying neural activity. In two experimental sessions, participants performed a letter two-back WM task after sham and either anodal or cathodal tDCS over the left dorsolateral pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
236
5
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(278 citation statements)
references
References 93 publications
(112 reference statements)
23
236
5
3
Order By: Relevance
“…In these studies researchers have applied anodal tDCS to the left prefrontal cortex with the consistent finding that stimulation improved verbal WM performance using 2-and 3-back WM tasks (Fregni et al, 2005a;Ohn et al, 2008;Andrews et al, 2011;Mulquiney et al, 2011;Zaehle et al, 2011). These results also showed that cathodal stimulation of the left prefrontal cortex did not improve accuracy on the task.…”
Section: Introductionsupporting
confidence: 53%
“…In these studies researchers have applied anodal tDCS to the left prefrontal cortex with the consistent finding that stimulation improved verbal WM performance using 2-and 3-back WM tasks (Fregni et al, 2005a;Ohn et al, 2008;Andrews et al, 2011;Mulquiney et al, 2011;Zaehle et al, 2011). These results also showed that cathodal stimulation of the left prefrontal cortex did not improve accuracy on the task.…”
Section: Introductionsupporting
confidence: 53%
“…In a related working memory task, the beneficial effects of anodal tDCS on performance accuracy developed during stimulation, and were stable for up to 30 min after the completion of stimulation [30] . Zaehle and co-workers [31] described similar positive effects of left prefrontal anodal tDCS on response accuracy in an n-back working memory task, while cathodal tDCS disturbed performance.…”
Section: Working Memorymentioning
confidence: 82%
“…Given the performancerelated alteration of oscillatory activity [31,40] , the contribution of theta activity to working memory performance was explored in subsequent studies. Left dorsolateral prefrontal oscillatory stimulation within the theta frequency range, as well as bilateral stimulation of the DLPFC, improved working memory [40,41] .…”
Section: Working Memorymentioning
confidence: 99%
“…Similarly, DBS can reverse hippocampal information processing deficits among in animals with a variety of developmental manipulations thought to model schizophrenia (Ewing and Grace, 2013;Klein et al, 2013;Perez et al, 2013). In humans, transcranial direct current stimulation has been used to induce changes in brain activity, suggesting that non-pharmacological approaches may also have promise in treating the abnormal underlying brain rhythms in the disorder (Zaehle et al, 2010(Zaehle et al, , 2011a(Zaehle et al, , 2011bKeeser et al, 2011;Jacobson et al, 2012). Patients are shown in blue and controls in red.…”
Section: Discussionmentioning
confidence: 99%